Interconnects and Interposer in Porous Anodic Aluminum Oxide: The Fabrication Technology and Process Integration. (19th July 2018) - Chan, Hsiang-Yu; Bachman, Mark; Li, Guann-Pyng
Abstract : Porous anodic aluminum oxide (AAO) features its interesting nanoporous structure which is capable of being used as a template for nanopatterning, highly anisotropic nanowire fabrication, and MEMs devices fabrication. In this work, AAO was demonstrated to be an interposer substrate for 2.5/3D packaging technology in microelectronics exploiting the unique etching characteristic of nanopores. Not only the high density vertical through via was fabricated but also metallized with Cu as void-less interconnect simply by using wet chemicals. Passive devices like inductors were embedded in AAO film after via metallization and re-distribution layer Cu electroplating which provide multifunctionalities to proposed AAO interposer. AAO with the special structural and etching properties plus its low electrical loss, thermal stability, and mechanical robustness, is a promising material for heterogeneous integration and advanced microelectronic packaging technology.